A Comparative Review on Bioremediation of Chromium by Bacterial, Fungal, Algal and Microbial Consortia. Issue 6 (1st June 2022) - Kuanar, Ananya; Kabi, Sandeep Kumar; Rath, Monalisa; Dhal, Nabin Kumar; Bhuyan, Ruchi; Das, Somadatta; Kar, Dattatreya
Abstract: Metals are necessary for plants and animals to function biologically, but presence of massive quantities can disrupt the metabolic activities in an organism's systems. Chromium has been classified between the top 20 harmful toxic material by the Agency for Toxic Compounds and Disease Registry. So a continuous environmental monitoring and a thorough understanding about chromium are highly essential particularly against soil-plant system. Bioremediation is gradually becoming the common practise for heavy-metal-contaminated soils restoration as it is cost active and environmentally friendly than that of traditional physical and chemical procedures, that are very ineffective as well as quite expensive especially when the concentrations of metal are low, which produces toxic sludge in a very significant amounts. So this is a comparative review on bioremediation of chromium by bacterial, fungal, algal and microbial consortia to check the bioremediation caused by different organism so that it will help further. This might be useful in designing new understanding into the growth and advancement of forthcoming technologies for upcoming research about bioremediation of chromium by the industrial scale.